(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article examines the use of text-based speech technology in teaching the Kyrgyz language in grades 5 of Russian schools. The main purpose of the study is to improve the quality of lessons through the development of language competencies, thinking skills and communication skills of students. The article describes the methods of text selection and analysis, involving students in the exchange of ideas and creative activities, as well as the development of writing and speaking skills. Working with text materials is not just a way to read or retell; It is a powerful pedagogical tool that comprehensively develops a student’s thinking, vocabulary, and ability to understand and use grammatical constructions. The results of the pedagogical experiment demonstrate the effectivenessof using the text method and offer practical recommendations. This research is aimed at increasing the level of knowledge and interest of students through the use of innovative ways of teaching the Kyrgyz language.